Assembling a hand-held trichotillometer and determination of epilation force in normal individuals - Kumaresan Muthuvel; Srinivas Chakravati; Sasidaharan Nair (Wolters Kluwer Medknow Publications, 2017)
Aim: To assemble a simple, inexpensive hand-held trichotillometer and to determine the epilation force (EF) required to pluck the anagen hair and telogen hair from four regions of the scalp in healthy volunteers. Materials and Methods: A simple hand-held trichotillometer was assembled by modifying a laboratory spring balance, and the instrument was calibrated after attachments. EF was measured in 30 healthy individuals on four regions of the scalp. Results: A total of 30 volunteers were included in the study, among them 15 were males and 15 were females. A total of 1200 hairs were examined. The mean EF in our study was 70.15 grams (g). The mean EF required to pluck the anagen hair was 86.61 g and telogen hair was 53.69 g. Conclusion: The assembled- hand held trichotillometer is a simple and reliable device. Tricotillometer is a useful device to measure the EF in various physiological and pathological conditions and may have diagnostic, prognostic, and therapeutic value in various hair diseases.